(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The Accountancy, Business, and Management (ABM) Strand provides students with the skills and knowledge they need to work in the corporate world. One of the necessary major subjects that they need to pass is accounting. Basic accounting is the practice of recording and reporting business transactions; it has five major accounts, that is, asset, liability, capital, revenue, and expense. Every student must have analytical thinking, critical thinking, and problem-solving skills. However, some students are still having struggles with their basic accounting subject to the point that their performance in basic accounting subject is affected. Several factors affecting why students do not understand the lessons about basic accounting include the following: they are slow to catch up with the lesson, and teachers are ineffective. Hence, we conduct a basic accounting tutorial among Grade 11 ABM students in Bestlink College of the Philippines. Descriptive method is used in this study. This study enhances their basic accounting skills through basic accounting tutorial in Bestlink College of the Philippines. It is necessary to identify the effectiveness of conducting basic accounting tutorial amongGrade 11 ABM students. A descriptive study determines and reports the way things are. Its concern is to enhance basic accounting skills of the students. The main instrument used is questionnaire, which is used to accumulate the data needed to answer the problems presented in chapter 1. The following factors affect the academic performance in accounting: student lacks English language proficiency, the student has no background about basic accounting, the student’s efforts toward the subject are insufficient, the student has bad study habits, the student only l has less time for solving accounting problems, the student has poor attendance, the student lacks analytic skills. Many factors affect the difficulties in accounting subject. The recommendations in improving the academic performance of students in accounting include the following: listen eagerly to the discussion of the teacher, attend the class, study in advance, study hard, and join accounting tutorial. For the students to not have struggles in accounting, they should listen eagerly and follow the direction to the discussions of the teachers for them to ease difficulties in basic accounting. The students must do an advance reading or study for them to have advance learning.